2018
DOI: 10.1007/s00464-018-6240-y
|View full text |Cite
|
Sign up to set email alerts
|

A predictive model for patients with median arcuate ligament syndrome

Abstract: Laparoscopic MAL produces significant symptom improvement, particularly in bodily pain. This is one of the first studies that uses preoperative data to predict symptom improvement following a MAL release. Age and baseline CA expiratory velocity can be used to guide postoperative expectations in patients with MAL syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 35 publications
3
9
0
1
Order By: Relevance
“…Similarly, Cienfuegos' study identified that patients with severe stenosis (>70%) experienced full resolution of symptoms in 71% of cases 16 . Brady's model further established that age and increased pre‐operative expiratory coeliac artery velocity were significant predictors of clinical improvement 17 . In our cohort, we reported a favourable post‐operative outcome for all patients with the same risk factors in conjunction with a low GSRS and VISICK score resulting in an early return to normal physical activities.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Similarly, Cienfuegos' study identified that patients with severe stenosis (>70%) experienced full resolution of symptoms in 71% of cases 16 . Brady's model further established that age and increased pre‐operative expiratory coeliac artery velocity were significant predictors of clinical improvement 17 . In our cohort, we reported a favourable post‐operative outcome for all patients with the same risk factors in conjunction with a low GSRS and VISICK score resulting in an early return to normal physical activities.…”
Section: Discussionsupporting
confidence: 74%
“…16 Brady's model further established that age and increased pre-operative expiratory coeliac artery velocity were significant predictors of clinical improvement. 17 In our cohort, we reported a favourable post-operative outcome for all patients with the same risk factors in conjunction with a low GSRS and VISICK score resulting in an early return to normal physical activities. Likewise, Ho reported that post-exertional pain and low VISICK scores were significantly associated with a high successful curative rate, whereas, abdominal pain at rest and vomiting along with higher VISICK scores were significantly associated with poorer outcomes.…”
Section: Discussionsupporting
confidence: 51%
“…Algumas controvérsias acompanham a síndrome, visto que aspectos do diagnóstico e tratamento não estão bem estabelecidos 2,5,13,15 . A maioria dos achados na literatura estão sedimentados em relatos de caso ou séries com poucos pacientes, mas os autores apontam a compressão do tronco celíaco pelo ligamento arqueado 4 , como a principal causa, presente em até 24% dos pacientes 13 . A incidência é estimada em 2/100.000 habitantes 11 .…”
Section: Discussionunclassified
“…To achieve this, both pre-and postoperative adjunctive therapies, along with the use of arterial reconstruction and stenting were used more often in these studies. [23][24][25][26][27][28][29] Therefore, the current literature makes accurate comparison of outcomes between pure treatment modalities difficult. The data also showed an increased conversion rate to open in laparoscopic studies compared to the data presented here.…”
Section: Literature Review and Summarymentioning
confidence: 99%
“…The data also showed an increased conversion rate to open in laparoscopic studies compared to the data presented here. [23][24][25][27][28][29]…”
Section: Literature Review and Summarymentioning
confidence: 99%